Pharmacogenetics of interaction between depot medroxyprogesterone acetate and efavirenz, rifampicin, and isoniazid during treatment of HIV and tuberculosis. Issue 1 (January 2022) - Haas, David W.; Mngqibisa, Rosie; Francis, Jose; McIlleron, Helen; Robinson, Jennifer A.; Kendall, Michelle A.; Baker, Paxton; Mawlana, Sajeeda; Badal-Faesen, Sharlaa; Angira, Francis; Omoz-Oarhe, Ayotunde; Samaneka, Wadzanai P.; et al.
Abstract : Objective: In AIDS Clinical Trials Group study A5338, concomitant rifampicin, isoniazid, and efavirenz was associated with more rapid plasma medroxyprogesterone acetate (MPA) clearance compared to historical controls without tuberculosis or HIV therapy. We characterized the pharmacogenetics of this interaction. Methods: In A5338, women receiving efavirenz-based HIV therapy and rifampicin plus isoniazid for tuberculosis underwent pharmacokinetic evaluations over 12 weeks following a 150-mg intramuscular injection of depot MPA. Data were interpreted with nonlinear mixed-effects modelling. Associations between individual pharmacokinetic parameters and polymorphisms relevant to rifampicin, isoniazid, efavirenz, and MPA were assessed. Results: Of 62 A5338 participants in four African countries, 44 were evaluable for pharmacokinetic associations, with 17 CYP2B6 normal, 21 intermediate, and 6 poor metabolizers, and 5 NAT2 rapid, 20 intermediate, and 19 slow acetylators. There were no associations between either CYP2B6 or NAT2 genotype and MPA C min at week 12, apparent clearance, C max, area under the concentration-time curve (AUC) or half-life, or unexplained interindividual variability in clearance, and uptake rate constant or mean transit time of the slow-release fraction ( P > 0.05 for each). In exploratory analyses, none of 28 polymorphisms in 14 genes were consistently associated with MPA pharmacokinetic parameters, and none withstood correction for multiple testing. Conclusions: Study A5338 suggested that more frequent depot MPA dosing may be appropriate for women receiving rifampicin, isoniazid, and efavirenz. The present results suggest that knowledge of CYP2B6 metabolizer or NAT2 acetylator status does not inform individualized DMPA dosing in this setting. Abstract : Supplemental Digital Content is available in the text.